The Impact of Virtual Reality Training on Sport Injury Rehabilitation – a Literature Review - Górniak, Aleksandra; Kubas, Aleksandra; Widawski, Michał; Gizińska, Natalia; Sobczyk, Aleksander; Lewandowska, Paulina; Rusiecka, Amelia (Quality in Sport, 2025)
Introduction and Purpose: Virtual reality (VR) technology is being studied more and more as an effective tool in sports injury rehabilitation. This review addresses current evidence concerning the application of VR in recovery from musculoskeletal and neurological injuries, control of pain, and psychological assistance, and potential roles in rehabilitation. State of Knowledge: Evidence indicates that rehabilitation with VR enhances patient engagement with immersive and interactive therapy, which can improve motor function, balance, and functional outcomes overall. VR is used in recovery rehabilitation of ligament injuries, orthopedic surgery, stroke, spinal cord injury, and traumatic brain injury. VR also proves effective as a non-pharmacological method of pain control, with a potential reduction in analgesic needs, such as opioids. Importantly, it was also shown that VR improves mental health by decreasing symptoms of anxiety, depression, and posttraumatic stress disorder, thereby convincing the audience about the overall benefits of VR-based rehabilitation. Methods The present paper searched the literature on electronic databases, including PubMed and ResearchGate, using the keywords "VR," "virtual reality injury," "virtual reality rehabilitation," "virtual reality pain," "virtual reality psychology," and "virtual reality cognitive function" Articles include randomized controlled trials, meta-analyses, and systematic reviews between 1999 to the present year, preferring the sources that were published from 2020 and onwards. Conclusions While VR offers a global, patient-centered approach that complements traditional rehabilitation methods, the scientific research in the field is meager. More studies are clearly warranted to establish VR’s long-term effects and full potential in rehabilitation. This review highlights the current shortcomings and future promise of VR-based rehabilitation in sports injury rehabilitation.